Effects of OCR on the static characteristics and microstructure of Yellow River silt - Wu, Yongmei; Wang, Wei; Chen, Yong; Wang, Tipu; Chai, Shaoqiang; Ding, Mengxiang; Du, Zibo (Frontiers in Earth Science, 2025)
The foundation soil is often over-consolidated due to the change of soil consolidation history in practical engineering. The effect of over-consolidation ratio (OCR) on the mechanical properties and microstructure of silt has not been sufficiently studied especially on the Yellow River alluvial silt. A series of triaxial undrained shear tests and corresponding SEM tests of the Yellow River alluvial silt were then carried out under different confining pressures and OCRs. The stress and strain curves of the silt show strain-hardening characteristics. The hardening characteristics become more significant, and the peak stress increases significantly as the confining pressure and OCR increase. The silt specimens show phase transformation behavior under a normal consolidation state, which is characterized by stages of initial contraction, temporary phase transformation, and later dilation. The silt tends to be more dilative for over-consolidated specimens and the dilation behavior was more obvious with higher OCRs. The deviatoric stress of the silt can be normalized by the consolidation pressure. The normalized undrained shear strength of the silt generally increased with OCR. The cohesion and internal friction angle of the silt increase with OCR increasing which behaved more like the typical clays as it has more silt content and clay content. The apparent porosity decreases and the average shape coefficient increases with the increase of confining pressure and OCR which shows the silt is denser and the grain shape is closer to circular under higher confining pressure and OCR. The relationship between macroscopic strength characteristics and the microscopic apparent porosity is also discussed. It shows that the macroscopic peak strength gradually decreases with the increase of the microscopic apparent porosity. Such behavior is mainly caused by the internal pore volume reduction and the rise in the contact area between soil particles.